Single-cell and single-nucleus transcriptomics of the dorsal root ganglion in neuropathic pain: cell-state remodeling and translational prospects - Xu-Ran Liao; Huan Zheng; Jiang-Yuan Luo; Bi-Xin Zheng (Journal of Translational Medicine, 2026)
Abstract Neuropathic pain remains a major unmet clinical challenge, as current therapies provide limited efficacy and poor tolerability. A major obstacle to developing effective analgesics is the pronounced cellular and molecular heterogeneity of the dorsal root ganglion (DRG), which integrates neuronal, glial, immune, and stromal responses to injury. Recent advances in single-cell RNA sequencing (scRNA-seq) and single-nucleus RNA sequencing (snRNA-seq) have enabled cell-type-resolved analyses of these responses and revealed disease-associated cellular states that are obscured by bulk tissue profiling, thereby offering new opportunities to redefine disease mechanisms and therapeutic priorities. This review synthesizes evidence from single-cell studies of peripheral nerve injury, diabetic painful neuropathy, and chemotherapy-induced neuropathy. Although these conditions share common biological processes, including neuronal state remodeling, disrupted glial homeostatic support, context-dependent immune responses, and extracellular matrix reorganization, they do not converge on a single conserved molecular program. Peripheral nerve injury is characterized by neuronal injury and repair states, reactive and metabolic glial remodeling, and neuroimmune recruitment and crosstalk. Diabetic neuropathy is associated with altered sensory coding, impaired satellite glial lipid support, and neurodegenerative remodeling. Chemotherapy-induced neuropathy exhibits substantial agent-specific heterogeneity, including subtype-selective neuronal vulnerability and metalloproteinase-dysregulated satellite glial states following paclitaxel treatment, as well as sex-associated fibrotic remodeling following bortezomib treatment. These cellular states may serve adaptive, maladaptive, or degenerative functions. However, because most available studies rely on single-time-point or repeated cross-sectional sampling, they cannot directly establish temporal progression or causal relationships. We further examine how human DRG atlases bridge experimental models and human disease by determining whether candidate molecular targets and cell states are conserved and by identifying their cellular localization. These datasets also highlight species-specific differences in neuronal organization and non-neuronal transcriptional programs that may limit the direct translation of findings from rodent models. Consequently, the primary translational value of DRG single-cell studies lies in elucidating disease mechanisms and prioritizing candidate therapeutic targets for further investigation. Advancing these discoveries toward clinical application will require complementary evidence from human genetics, human DRG transcriptomic datasets, functional validation studies, and clinical pharmacology. Collectively, these complementary approaches may facilitate the development of mechanism-based and cell-type-informed analgesic strategies.